The Financing literacy project : key findings and reflections on Adult Literacy Benchmark 12 - Cobbett, Mary (2011)
Reports on the findings of the financing literacy project commenced in 2010, five years after the International Benchmarks on Adult Literacy were publised by the Global Campaign for Education. Looking specifically at Benchmark 12, its objective was to collect data on what governments are actually spending in this sector.